Financing of Preschool Education in Ukraine in 1919–1933: Historical and Legal, Historical and Economic Aspects - S. O. Tkachenko; О. V. Golovko (Law and Safety)
Historical and legal, historical and economic aspects of the process of formation and development of the system of public preschool education in Ukrainian SSR in 20s – early 30s of the XX century have been analyzed.